Root and Root Canal Morphology Classification Systems - Mohmed Isaqali Karobari; Ayesha Parveen; Mubashir Baig Mirza; Saleem D. Makandar; Nik Rozainah Nik Abdul Ghani; Tahir Yusuf Noorani; Anand Marya (International Journal of Dentistry)
Introduction. While there are many root morphology classification systems with their own distinct advantages, there are many shortcomings that come along with each system. Objectives. The aim of this review was to compare the various root and root canal morphology classifications, their advantages, limitations, and clinical and research implications. Data Sources and Selection. An extensive literature search was conducted on PubMed and Scopus to identify the published data on root and root canal classification systems published until 1 May 2020 using keywords, root canal classification system, classification systems for root canals, and root morphology. The related literature was reviewed and then summarized. Data Synthesis. Several studies have analysed and detailed root and root canal classifications and further added new subsystems, works of Weine et al. (1969) and Vertucci et al. (1974). Besides, Sert and Bayirli (2004) added supplementary types to Vertucci’s classification system. A new classification was most recently introduced by Ahmed et al. (2017) involving the use of codes for tooth numbering, number of roots, and canal configuration. Conclusions. Weine et al. classified only single-rooted teeth, without considering multirooted teeth and complex configurations. Vertucci’s classification included complex configurations, with Sert and Bayirli adding further complex supplemental types. Ahmed et al.’s classification simplifies classifying root and canal morphology while overcoming the limitations of several previous classification systems making it beneficial for implementation in dental schools.